2016
DOI: 10.1152/ajpheart.00887.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin A deficiency in the postnatal mouse heart: role of hepatic retinoid stores

Abstract: To determine whether hepatic depletion of vitamin A (VA) stores has an effect on the postnatal heart, studies were carried out with mice lacking liver retinyl ester stores fed either a VA-sufficient (LRVAS) or VA-deficient (LRVAD) diet (to deplete circulating retinol and extrahepatic stores of retinyl esters). There were no observable differences in the weights or gross morphology of hearts from LRVAS or LRVAD mice relative to sex-matched, agematched, and genetically matched wild-type (WT) controls fed the VAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…To evaluate the current reporting of echocardiographic results, we accessed PubMed on July 21, 2017, and searched for “mouse and American Journal of Physiology and (echocardiography or echocardiographic or ultrasound).” This search resulted in 437 articles, of which 52 articles were published between January 1, 2016, and present as well as 14 articles that were excluded as false positives (two kidney, one liver, one lung, one bone, one RV, two rat not mouse, one fetal not adult, and five with no cardiac echocardiography results). The remaining 38 articles were analyzed both for completeness of information provided and for quality assessment of the echocardiography values reported ( 11 , 13 , 22 , 27 , 30 , 36 , 38 , 39 , 42 , 45 , 52 , 54 , 57 , 59 , 65 , 70 , 75 , 76 , 78 , 85 , 102 , 114 , 117 119 , 132 , 147 , 148 , 158 , 160 , 165 , 170 , 172 , 182 , 187 , 193 , 201 , 206 ).…”
Section: Echocardiographymentioning
confidence: 99%
“…To evaluate the current reporting of echocardiographic results, we accessed PubMed on July 21, 2017, and searched for “mouse and American Journal of Physiology and (echocardiography or echocardiographic or ultrasound).” This search resulted in 437 articles, of which 52 articles were published between January 1, 2016, and present as well as 14 articles that were excluded as false positives (two kidney, one liver, one lung, one bone, one RV, two rat not mouse, one fetal not adult, and five with no cardiac echocardiography results). The remaining 38 articles were analyzed both for completeness of information provided and for quality assessment of the echocardiography values reported ( 11 , 13 , 22 , 27 , 30 , 36 , 38 , 39 , 42 , 45 , 52 , 54 , 57 , 59 , 65 , 70 , 75 , 76 , 78 , 85 , 102 , 114 , 117 119 , 132 , 147 , 148 , 158 , 160 , 165 , 170 , 172 , 182 , 187 , 193 , 201 , 206 ).…”
Section: Echocardiographymentioning
confidence: 99%
“…Although the exact mechanisms are still under investigation, the published data indicate that inhibition of ErbB2 results in increased generation of reactive oxygen species (28, 41) , downregulation of pro-survival PI3K/AKT signaling (48) and improper functioning of excitation–contraction coupling machinery and loss of contractile function (44) . Recently, we have shown that endothelial cells represent one of the major subpopulations of proliferating cells in the adult heart (3) , indicating endothelial renewal in vivo . Our current findings suggest that ErbB2-targeted therapy may prevent endothelial differentiation of highly proliferative cells and perhaps contribute to endothelial dysfunction and development of cardiomyopathy (29) .…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models of obesity, atRA-treatment prevented fibrosis and cardiomyocyte apoptosis (Manolescu et al, 2014). Conversely, in rodent models of myocardial infarction, vitamin A insufficiency was associated with adverse ventricular remodeling (Asson-Batres et al, 2016;Minicucci et al, 2010). These observations are also supported by evidence that mice deficient in β-carotene-15,15'-dioxygenase (BCO1), the enzyme required to convert provitamin A carotenoids to retinol, also exhibit systolic dysfunction (Hessel et al, 2007;S.…”
Section: Role Of Atra In the Development And Function Of Cardiac Fibroblastsmentioning
confidence: 93%